Future potential of economic impact assessment. Issue 4 (3rd July 2020) - Williams, Galina
ABSTRACT: Economic impact assessment (EcIA) has attracted some criticism due to its limited focus. Typically, EcIA is used to validate the proposed proposals based on growth in income and employment. This paper argues that EcIA should play a more active and stronger role in impact assessment. For example, the impacts of the proposed projects should be assessed using the economic development goals rather than only changes in economic growth. The conceptual framework for the comprehensive impact assessment is discussed. Examples of indicators that can be used in relation to sustainable development goals are provided.